Comparison of Granitoid Characteristics West Kalimantan and Karangsambung Based On Mineralogical And Geochemical Aspects - Kevin Setyo Adi Nugroho; Iwan Setiawan; Tri Winarno (UIR PRESS, 2021)
Indonesia was included in the ring of fire so that it has various types of tectonic products, one of which is granitoid. Granitoid is very complex rock and many are found in Indonesia. Some of them are found in West Kalimantan and Karangsambung. Basis of the reasearch is there is no research that compares granitoid in two regions. The purpose of this study was to compare rock characteristics and granite petrogenesis of West Kalimantan and Karangsambung. The research method used was collecting data on field, also laboratory analysis of rock samples using a polarization microscope, refraction microscope, and X-Ray Fluorescence analysis. The mineralogical characteristics of each study area tend to be almost the same. The predominant composition of the main minerals is quartz, plagioclase and orthoclase. But specifically the rock samples from West Kalimantan have been altered from phylic-silicification-propylitic. The entire study area contained accessory minerals, namely apatite, zircon, titanite, and for monazite only in the West Kalimantan sample. There was mineralization up to the supergene stage in the presence of the characteristic minerals for the supergene covelite and chalcocytes in the West Kalimantan sample. Geochemical analysis of both regions shows the same magma affinity, namely Calc Alkaline - High K Calc Alkaline. For West Kalimantan, the value of A / CNK <1.1 has a type metaluminious and > 1.1 a type peraluminious. Meanwhile, Karangsambung A / CNK value <1.1 has a type metaluminious. So that West Kalimantan granite has two I-type and S-type. While Karangsambung is I-type. West Kalimantan granite is formed in continental arc granite (CAG) and continental collision granite (CCG). Meanwhile, Karangsambung in Volcanic Arc Granite (VAG). It can be concluded that the granites of the two regions have quite different characteristics even though they belong to a relatively similar tectonic environment.